The analysis of profitability and productivity of dairy cattle enterprises in konya province and their production and marketing problems - Aytekin Günlü; Engin Sakarya (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the profitability and productivity measures to be taken up order to increase the optimum level in resource use by constructing an econometric model using the production and financial data from randomly selected 135 dairy cattle enterprises in Konya between 1995 and 1996. Data were analyzed by the Cobb-Douglas production lunction. economic rantability and rantability factor ratios Enterprises were evaluated on both scale and the province bases The cost components estimated and their proportion in the total cost in this research were as follows: 49.99 % in feed. 32.78 % in labour, 7.18 % in depreciation cost, 4 69 % in veterinary services 1 41 % in maintenance cost and 3 93 % in other costs. îhe income sources and their proportions in the total income in these enterprises in 1995 were as follows: 62.04 % in milk sales, 25.27% in calf revenues, 10.98 % inventory value increases, 1 71 % manure revenues These values were estimated to be 51.52%, 17.96 %, 31 95 %. and 0 82 %, m 1996 respectively. The average milk production was calculated to be 3530 I and 3260 I in 1995 and 1996 respectively The ratio of economic rantability was estimated to be -5.46 and 30.14 in 1995 and 1996 respectively. Rantability factor ratio was estimated to be -13 08 and 34.75 in this period Large scale enterprises had more profit in 1995, whereas the medium scale enterprises had higher profit in 1996. According to the tesults of multiple regresion analysts the Marginal Value Productivity of input factors at leed, labour, depraciation costs, veterinary services, maintanence costs and the other costs were 0.81, 0.91; 6.30: 1.84; -5.63 and 5.73 respectively Returns to scale in Konya was 1.076. It was concluded that the effectiveness of resource usage of input factors which are used throughout the production period in dairy cattle enterprises in the province was inefficient In other words, the level of resource use was far from the optimum level for profil maximization.